2010
DOI: 10.1007/s11664-010-1153-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of AlGaN/GaN Heterostructures Grown on Vicinal Substrates

Abstract: We report on the growth of Al 0.25 Ga 0.75 N/GaN heterostructures grown on low dislocation density vicinal surfaces of semi-insulating c-axis GaN substrates. Atomic force microscopy (AFM), photoluminescence (PL), cathodoluminescence (CL), high-resolution x-ray diffraction (HRXRD), secondary-ion mass spectroscopy (SIMS), Hall effect, and Raman spectroscopy have been used to assess structural and electrical properties as a function of substrate offcut. Bulk GaN substrates with vicinal offcut between 0.5°and 1.4°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…3 However, very few reports on the effects of offcut of bulk GaN substrates on subsequent epitaxy exist in the literature, and these are primarily concerned with the growth of InGaN as compared to AlGaN. 4,5,6 This work aims to elucidate the effect of the surface offcut on the compositional and electrical performance of AlGaN/GaN heterostructures on bulk GaN substrates.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, very few reports on the effects of offcut of bulk GaN substrates on subsequent epitaxy exist in the literature, and these are primarily concerned with the growth of InGaN as compared to AlGaN. 4,5,6 This work aims to elucidate the effect of the surface offcut on the compositional and electrical performance of AlGaN/GaN heterostructures on bulk GaN substrates.…”
Section: Introductionmentioning
confidence: 99%
“…al reported that UV photoenhanced chemical etching of the GaN substrates reduced the concentration of Si at the interface, but did not completely eliminate it [3]. As a result, impurities including Fe [3,4], C [2] and Mg [5] have been added to compensate the remaining Si donors.…”
mentioning
confidence: 99%